Kinematic differences between normal and low arched feet in children using the Heidelberg foot measurement method - Twomey, Dara; McIntosh, A. S.; Simon, Jan; Lowe, K.; Wolf, Sebastian Immanuel (Gait & posture, 2010)
The purpose of this study was to investigate the kinematics of normal arched and low arched feet in children and use this data to quantify the differences between the two foot types during walking gait. Multi-segment foot motion was measured, using the Heidelberg foot measurement method (HFMM), for 25 normal arched feet and 27 low arched feet in 9-12-year-old children. The kinematic differences in the foot between the two groups during walking were relatively small, except for the medial arch and forefoot supination angles. The magnitude of the medial arch angle was approximately 10° greater in the low arched group than the normal arched group throughout the gait cycle. There was a significant difference found in the forefoot supination angle (p<0.03), relative to the midfoot, between the two groups at initial heel strike, and maximum and minimum values throughout the gait cycle. The values for the normal group were significantly higher in all these angles indicating that the forefoot of the low arched foot remains less pronated during the gait cycle. There was no significant difference in the motion of the rearfoot between the two foot types. The results of this study provide normative values for children's feet and highlight the mechanical differences in flexible flat feet in this age group. This data contributes to knowledge on foot kinematics in children and will be valuable for future research on the structure, function and potential treatment of the flexible flat foot.
Gesehen am 26.01.2024